PENGARUH KEAHLIAN, INDEPENDENSI DAN ETIKA TERHADAP KUALITAS AUDITOR PADA INSPEKTORAT KABUPATEN BULUKUMBA - Nurfaidah Nurfaidah (AkMen JURNAL ILMIAH, 2019)
The purpose of this research include to obtain empirical evidence to investigate and analysis of the influence of expertise , independence and ethics on the quality of auditors inspectorate bulukumba on district . Sample chosen overall as many as 30 auditors/ examiner. A model of analysis that was used to test hypotheses is linear regression of multiple , this analysis we can based on the figures for the data from 31 the number of respondents who back out of the research obtained through a questionnaire .The independent variable been disclosed in the research this is craftsmanship , the independence of the and ethics .To using three dependent variables in this research was the quality of an auditor .Data in the research is the primary data was obtained from disseminating questionnaires directly to the whole an auditor/ Bulukumba district inspectorate examiner. This research result indicated in partial expertise a significant positive impact on the quality and independence of auditors and ethics influential positive who do not significantly to the quality of the auditors / an examiner in inspectorate. bulukumba districtIn bersama-sama ( simultaneous ), expertise independence of, and ethics influential positive who do not significantly to the quality of the auditors in inspectorate. bulukumba district. Tujuan penelitian ini antara lain untuk memperoleh bukti empiris guna mengetahui dan dianalisis tentang pengaruh keahlian, independensi dan etika terhadap kualitas auditor pada Inspektorat Kabupaten Bulukumba. Sampel dipilih secara total sebanyak 30 auditor/pemeriksa. Model analisis yang digunakan untuk menguji hipotesis adalah regresi linier berganda, analisis ini didasarkan pada data dari 31 responden yang penelitiannya melalui kuesioner. Variabel independen dalam penelitian ini adalah keahlian, independensi dan etika. Untuk variabel dependen dalam penelitian ini adalah kualitas auditor. Data dalam penelitian ini merupakan data primer yang diperoleh dari penyebaran kuesioner secara langsung kepada seluruh auditor/pemeriksa Inspektorat Kabupaten Bulukumba. Hasil penelitian ini menunjukkan secara parsial keahlian berpengaruh positif yang signifikan terhadap kualitas auditor sedangkan independensi dan etika berpengaruh positif yang tidak signifikan terhadap kualitas auditor/pemeriksa pada Inspektorat Kabupaten Bulukumba. Secara bersama-sama (simultan) keahlian, independensi, dan etika berpengaruh positif yang tidak signifikan terhadap kualitas auditor pada Inspektorat Kabupaten Bulukumba.